Fish oil coupling with therapeutic ultrasound facilitates healing of ruptured achilles tendon - Chan, K. O. W.; Tong, H. H. Y.; Ng, G. Y. F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Achilles tendon rupture is common in athletes but there is no consensus on the optimal treatment. Fish oil is rich in omega-3 fatty acids (n-3) and has been shown to suppress inflammation (Calder, 2013), promote collagen synthesis (Hankenson et al., 2000) and hence enhance connective tissue healing. Therapeutic ultrasound has long been reported to be effective for treating soft tissue injuries. The aims of the present study were to investigate the effect of topical fish oil coupled with ultrasound on healing of partial Achilles tendon rupture in a rat model. Methods: Eighty five Sprague-Dawley rats with surgically hemi-transected right Achilles tendons were randomly assigned into four groups ie. topical placebo ointment as control (CON), topical fish oil (FO), ultrasound (US) and combination of ultrasound and fish oil (FU). Half of the animals were treated for 2 weeks while the rest were treated for 4 weeks. The right Achilles tendons were harvested after the treatment period for biomechanical assessments including structural stiffness and ultimate tensile strength (UTS). The values after normalization with the intact Achilles tendon were then compared between groups and treatment duration using twoway analysis of variance (ANOVA). Results: The FU group demonstrated significant improvement in structural stiffness and UTS than CON at 4 weeks (p<0.05). Significantly higher UTS was observed in US than CON for both treatment periods (p<0.05). The FO group had increased structural stiffness at 4 weeks (p<0.05) than CON. Discussion: Our findings revealed that fish oil either applied alone or incorporated with ultrasound improved biomechanical properties of injured tendon for longer treatment period. Although the actual mechanism behind is not certain, it is possible that the role of n-3 as a cyclooxygenase (COX) inhibitor may contribute to the positive findings as agreed with Virchenko et al. (2004). COX is an enzyme signaling pain and inflammation and hence n-3 suppress inflammation (Calder, 2013). In addition, our findings revealed that therapeutic ultrasound is effective in promoting tendon healing, which is consistent with the previous studies (Ng et al., 2003; Yeung et al., 2006).